Arboviral diseases in pediatrics - Marlos Melo Martins; Arnaldo Prata-Barbosa; Antonio José Ledo Alves da Cunha (Elsevier, 2020)
Objectives: To present the currently available evidence on transmission, clinical, diagnostic methods, treatment, and prevention methods of major arboviruses that occur in childhood. Source of data: Non-systematic review carried out in MEDLINE (PubMed), LILACS (VHL), Scopus, Web of Science, Cochrane, CAPES Portal, and Google Scholar databases for the past five years using the search terms arboviruses, dengue, chikungunya, Zika, Mayaro, and West Nile fever, as well as child, newborn, and adolescent. Synthesis of data: The main characteristic of arboviruses is the fact that part of their replication cycle occurs inside insect vectors, thus being classically transmitted to humans through the bite of mosquitoes (hematophagous arthropods), although non-vector transmission of these viruses is also possible in specific situations. These diseases remain a major public health challenge, due to the lack of specific antiviral treatment, the co-circulation of different arboviruses in endemic/epidemic regions, the lack of effective and safe immunizations for the vast majority of these viruses, and the great difficulty in vector control, especially in large urban centers. Conclusions: Children are especially vulnerable to this group of diseases due to characteristics that facilitate the development of the most severe forms. More detailed knowledge of this group of diseases allows the pediatrician to diagnose them earlier, implement the correct treatment, monitor warning signs for the most severe forms, and establish effective preventive measures. Resumo: Objetivos: Apresentar as evidências atualmente disponíveis sobre transmissão, quadro clínico, métodos diagnósticos, tratamento e métodos de prevenção das principais arboviroses que ocorrem na infância. Fonte de dados: Revisão não sistemática feita nas bases de dados Medline (Pubmed), Lilacs (BVS), Scopus, Web of Science, Cochrane, portal Capes e Google Scholar nos últimos cinco anos, com o uso dos termos arboviroses, dengue, chikungunya, zika, mayaro, febre do oeste do Nilo e criança, recém-nascido, adolescente. Síntese de dados: Os arbovírus têm como característica principal o fato de parte de seu ciclo de replicação ocorrer em insetos vetores. Assim, são classicamente transmitidos aos seres humanos pela picada de mosquitos (artrópodes hematófagos), embora seja também possível a transmissão não vetorial desses vírus em situações específicas. Essas doenças ainda constituem um grande desafio na saúde pública, devido à inexistência de tratamento antiviral específico, à cocirculação de diferentes arbovírus em regiões endêmicas/epidêmicas, à falta de imunizações efetivas e seguras para a grande maioria desses vírus e à grande dificuldade do controle vetorial, em especial nos grandes centros urbanos. Conclusões: As crianças constituem um grupo especialmente vulnerável a esse grupo de doenças, pois têm características que facilitam o desenvolvimento das formas mais graves. O conhecimento mais detalhado desse grupo de doenças permite ao pediatra diagnosticar mais precocemente, instituir o tratamento correto, vigiar os sinais de alarme para as formas mais graves e colocar em prática efetivas medidas de prevenção. Keywords: Arboviruses, Child, Newborn, Dengue, Chikungunya, Zika, PALAVRAS-CHAVE: Arboviroses, Crianças, Recém-nascidos, Dengue, Chikungunya, Zika